Elementary Teacher Professionalism and Workload: Case Study at Palopo City Elementary School - Munir Yusuf; Muhammad Yaumi; Moh. Sain Hanafi (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo, 2021)
This study describes teacher performance by quantifying every detail of teacher activity. This research results from a case study conducted for eight months in elementary school. The research focuses on the workload of primary school teachers. This research data collection through observation, interviews, and document review. This research was conducted at SD Negeri 18 Maroangin and SD Islam Terpadu Madan Insan Palopo City, South Sulawesi Province. The study results are as follows: (1) Based on the implementation time, to complete all tasks, the workload of elementary school teachers takes 17 hours a day. Therefore, it equates to 102 hours per week. In this case, the teacher experiences an